Against Fraud: How Religious-Based Values Accounting Work - Sarmigi, Elex; Rahayu, Sri; Puspa Arum, Enggar Diah; Wijaya Z, Rico (TSAQAFAH, 2025)
Fraud is a widespread issue that can cause significant harm across various sectors, including government, business, and educational institutions. Several theories, such as the Fraud Triangle, Fraud Diamond, and Fraud Hexagon, have been developed to understand the factors that drive individuals to commit fraud. This research aims to analyze the role of religiosity values in minimizing fraudulent actions using a qualitative method and a literature study approach. Data were collected through an analysis of literature from journals, books, and previous research that examined the relationship between religiosity and fraudulent behavior. The findings indicate that religiosity plays a significant role in reducing individuals' intention and opportunity to commit fraud. Individuals with a good understanding of religion tend to have a stronger moral awareness, making it more difficult for them to rationalize fraudulent actions. Furthermore, religious values can help individuals manage pressure and suppress ego/arrogance, which are key elements in the Fraud Hexagon theory. Although religiosity serves as a deterrent to fraud, this study also finds that external factors such as opportunity and collusion continue to contribute to fraudulent behavior.